From Inquisitores Sedis Apostolicae to enquêteurs de Roi: franciscans in France in the first half of the 13th century - Elena Sergeevna Kravtsova (Религия, церковь, общество, 2016)
In the period 1226−1247 the order of the friars minor was in search of its social identity. This process influenced the administrative policy of the Pope and the French Crown. In the 1220s the Franciscans founded a lot of convents in South France which had no stable power institutions. The Franciscan order was to fill the vacuum of power. This capability was used by Gregory IX, the Pope. In the «Vita Prima» (1228−1230) Thomas of Celano created an image of alter Franciscus for Pope, who partly inherited Franciscus’ power over the order as the successor of his humility. So the Pope could use the Friars as inquisitors and fiscals. Further, the friars were used also by episcopal courts. Therefore, «Vita secunda» (1244−1247) excluded the possibility of alter Franciscus’ existence outside of the order. But in 1247 curia regis sent the friars to investigate bailli’s abuse of the royal power. It is argued that such employment was possible, because the King had appropriated «Franciscan» pietas. The «Vita Secunda» represented doctrine of piety, that taught, how to affect mundus and to turn from vice to grace. Further this idea would be developed by Bonaventure in his sermons to the royal family in the second half of the 13th century.